2021
DOI: 10.3390/ijerph18031016
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Pandemic Facilitate Mobile Payment? An Investigation on Users’ Perspective under the COVID-19 Pandemic

Abstract: Owing to the convenience, reliability and contact-free feature of Mobile payment (M-payment), it has been diffusely adopted in China during the COVID-19 pandemic to reduce the direct and indirect contacts in transactions, allowing social distancing to be maintained and facilitating stabilization of the social economy. This paper aims to comprehensively investigate the technological and mental factors affecting users’ adoption intentions of M-payment under the COVID-19 pandemic, to expand the domain of technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
173
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(201 citation statements)
references
References 50 publications
24
173
2
2
Order By: Relevance
“…All of the items were developed based on previous research and the opinions of relevant experts and academics to ensure they were valid. Each construct was measured using four items each from the following sources: perceived susceptibility from Yuen et al ( 7 ) and Huang et al ( 31 ); perceived severity from Huang et al ( 31 ); perceived benefits from Zhao and Bacao ( 8 ) and Park et al ( 57 ); perceived barriers from Huang et al ( 31 ), Zhao and An ( 24 ), Jensen et al ( 58 ), and Wang et al ( 59 ); trust from Zhao and Bacao ( 8 ); attitude from Chatzisarantis et al ( 60 ); and behavioral intention from Ma ( 2 ) and Yuen et al ( 7 ). A five-point Likert scale ranging from 1 = “strongly disagree” to 5 = “strongly agree” was used to evaluate these items.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the items were developed based on previous research and the opinions of relevant experts and academics to ensure they were valid. Each construct was measured using four items each from the following sources: perceived susceptibility from Yuen et al ( 7 ) and Huang et al ( 31 ); perceived severity from Huang et al ( 31 ); perceived benefits from Zhao and Bacao ( 8 ) and Park et al ( 57 ); perceived barriers from Huang et al ( 31 ), Zhao and An ( 24 ), Jensen et al ( 58 ), and Wang et al ( 59 ); trust from Zhao and Bacao ( 8 ); attitude from Chatzisarantis et al ( 60 ); and behavioral intention from Ma ( 2 ) and Yuen et al ( 7 ). A five-point Likert scale ranging from 1 = “strongly disagree” to 5 = “strongly agree” was used to evaluate these items.…”
Section: Methodsmentioning
confidence: 99%
“…Globally, COVID-19 remains one of the most serious threats to public health despite the recent development and distribution of COVID-19 vaccines (6)(7)(8). From May 24 to May 30, 2021, the number of new COVID-19 cases and deaths continued to decrease, with over 3.5 million new cases and 78,000 new deaths reported globally.…”
Section: Introductionmentioning
confidence: 99%
“…Data reported by the online payment operator PayPal on rising revenue and the number of registered transactions may serve as a measure of the change in consumer payment behavior on a global scale, indicating the increasing importance of e-commerce [38,39]. The change in consumer payment behavior has been not only analyzed in the context of cashless payments [40], but also has been analyzed from the viewpoint of its impact on the economy. Bounie et al [41] showed that the increased importance of e-commerce has reduced the shock caused by the pandemic in some sectors of the French economy.…”
Section: Literature Review-payment Behavior During the Covid-19 Pandemicmentioning
confidence: 99%
“…In this case, the majority of studies focuses on innovation drivers and barriers of adoption, as well as on the relationship between mobile innovations and their impact on regions, financial inclusion, customers' well-being (Nejad 2016 1 ;Weichert 2017;Górka 2018;Szumski 2020;Tang et al 2021). In the case of payment innovations, the extant literature characterizes particular types of new developments: e-wallets (Górka 2016;Yang et al 2021;Daragmeh et al 2021), online and mobile payments (Li et al 2020;Hwang et al 2021;Zhao and Bacao 2021) and digital currencies (Goodell et al 2021;Civelek et al 2021). These analyses are conducted mostly for selected countries or geographical locations, as cultural and demographic factors are important drivers of innovation adoption.…”
Section: Authormentioning
confidence: 99%